2013
DOI: 10.3168/jds.2012-5576
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of different whey concentrations on physicochemical characteristics and viable counts of starter bacteria in dairy beverage supplemented with probiotics

Abstract: Fermented dairy beverages supplemented with the probiotics Lactobacillus acidophilus and Bifidobacterium lactis containing different concentrations of whey in their formulas (0, 20, 35, 50, 65, and 80%, vol/vol) were processed and checked for pH; proteolysis; levels of glucose, lactose, ethanol, acetic acid, lactic acid, diacetyl, and acetaldehyde; and lactic bacteria and probiotic counts. The results allowed the effect of whey concentration on the dairy beverages to be observed for each of the different param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…Similar counts were found by Sarvari et al (2014) in yoghurts and by Castro et al (2013a) in probiotic dairy beverages. Previous studies have reported a slight increase of S. thermophilus counts during storage up to 1 week, followed by a decrease in yogurt (Birollo et al, 2000;Dave and Shah, 1997a, b).…”
Section: Survival Of Acid Lactic Bacteria During Storage Of Fermentedsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar counts were found by Sarvari et al (2014) in yoghurts and by Castro et al (2013a) in probiotic dairy beverages. Previous studies have reported a slight increase of S. thermophilus counts during storage up to 1 week, followed by a decrease in yogurt (Birollo et al, 2000;Dave and Shah, 1997a, b).…”
Section: Survival Of Acid Lactic Bacteria During Storage Of Fermentedsupporting
confidence: 76%
“…Ranadheera et al (2012) observed a decrease in pH up to the 7th day and an increase after this period, demonstrating unusual behavior as in the present study and unlike what has been shown in other studies. Kailasapathy et al (2008) obtained a pH decrease in fermented dairy beverages and Castro et al (2013a) observed pH stability for 80 days. Table 4, the acidity values of fermented dairy beverage vary from 0.69 (trial E) -0.97 (trial F) g of lactic acid/100 g. These results are in accordance with Powder milk concentration expressed in g&100 g beverage, **X 2 : Ricotta cheese whey concentration expressed in g&100 g beverage Table 4: Acidity values of fermented dairy beverage during the refrigerated storage Analysis performed in triplicate; values expressed in g lactic acid &100 g Different lowercase letters in the same row in indicate presence of statistical difference (p<0.05) among the treatments (fermented dairy beverage) along the storage days, according with the Tukey Test.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have investigated options for new uses of this byproduct, especially with the development of dairy beverages (CASTRO et al, 2013a;CASTRO et al, 2013b;MAITY;KUMAR;MISRA, 2008;PAVUNC et al, 2009). Whereas the biological oxygen demand of whey is high, it is possible to prevent environmental pollution caused by improper disposal of cheese whey (ALMEIDA; BONASSI; ROÇA, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, to exert their beneficial effects, probiotics should remain viable during the entire shelf life of the product (ROY, 2005). Gomes and Malcata (1999) emphasized that manufacturers must ensure the minimum number of viable cells in the product at the time of consumption.…”
Section: Introductionmentioning
confidence: 99%